Effect of Giving Turmeric Flour (Curcuma domestica) on Differential Leukocytes, Antibody Titers of Avian Influenza and Newcastle Disease Super Native Chickens - Nur, Adyatma Muhammad; Purwanti, Sri; Rahardja, Djoni Prawira; Mutisari, Dewi (ANIMAL PRODUCTION, 2023)
In order to raise super-native chickens without the usage of antibiotics, herbal plants with a phytobiotic function may be used as feed additions. This study aims to examine the effect of turmeric flour (Curcuma domestica) given through drinking water on leukocyte differentials, AI antibody titers, and ND antibody titers as indicators of immunity status in super-native chickens. Five treatments and four tests, each with five super native chicks, were used in the experiment, which was carried out utilizing an experimental methodology. The treatment (P) given included P0 as a negative control (drinking water without treatment), P1 as a positive control (drinking water + 0.1 g/L PromuneCÂ®), P2 (drinking water + 1 g/L turmeric flour), P3 (drinking water + 3 g/L turmeric flour) and P4 (drinking water + 5 g/L turmeric flour). All the data gathered for this study were evaluated using Analysis of Variance, and Duncan's test using SPSS version 25 was required if there were any significant differences. The 56-day-old AI and ND antibody titer reached a protective level where the best dose for AI antibody titer increase was 5 g/L of drinking water with AI log2 9.5 of titer and the best dose for ND antibody titer increase was 3 g/L of drinking water with ND log2 7.5 of titer. According to statistical analysis, the addition of turmeric powder to drinking water had no discernible effects on the mean of lymphocytes, monocytes, or eosinophils but had a significant impact (P0.05) on the mean of basophils. The treatment also had a noticeable effect on AI antibody titers (P<0.05) but had no noticeable effect on ND antibody titers. In conclusion, giving turmeric powder (Curcuma domestica) in drinking water is useful as an immunomodulator by maintaining normal levels of differential leukocytes, and increasing protection against AI and ND super-native chicken so it can be used as a natural feed additive.